Proyecto arquitectónico paisajístico del mercado municipal y su entorno inmediato integrando arquitectura sostenible en el cantón Montalvo - Chiquito Ávila, Christian Iván (2017)
The project aims to design a new Municipal Market in the Canton Montalvo, through a functional, landscape and environment friendly, to contribute to the orderly development of its environment. The municipal markets are a key point of reference for the financial progress of the people, arketing in the markets, is directly related to the distribution of basic necessities for the population, creating sources of work and contributes to the improvement of tourism, Cultural and economic importance of the place where it is built….